THE INFLUENCE OF WEATHER CONDITIONS ON THE FORMATION OF MEADOW CLOVER PRODUCTIVITY ON THE RIGHT BANK OF THE FOREST-STEPPE OF UKRAINE - Polevoy, A. M.; Bozhko, L. E.; Barsukova, E. A. (Scientific Progress & Innovations, 2021)
This article presents the results of studying the impact of weather conditions on the growth, development and yield formation of meadow clover, as the cultivation of perennial grasses is the basis for providing the fodder base for growing animals. In order to perform the task, the data of observations on the productivity of meadow clover in the second year of life and meteorological elements for the period from 1995 to 2015 were analyzed. The analysis of weather conditions’ effect on productivity formation included weather conditions of clover overwintering and conditions during the growing season from vegetation restoration to seed collection. The studies of the yield series of clover hay and seeds have shown that the trend of the yield of double-cutting clover hay and seeds is raising, the annual increase in hay yield according to the trend is 2.94 hundredweight/ha. Annual deviations of yields from the trend line due to the influence of weather in each particular year ranged from –3 hundredweight/ha to +20 hundredweight of hay per hectare. The dynamics of clover seed yields also tended to grow, but the increase was weak and averaged to 0.0023 hundredweight/ha annually. It has been determined that among the numerical indicators that influence the value of clover yield, overwintering conditions play a significant role. On the Right Bank, the probability of very low absolute minimal temperatures of –18… –19 °C at the depth of the root collar of clover is about 7 %. The probability of absolute minimal temperatures at the level of critical freezing of meadow clover, which is –15… –16°С, is respectively 12 % and 13 %. The analysis of the values of correlation coefficients between clover seed yields and different indicators has shown that the most significant role in the formation of meadow clover productivity is played by the combination of several individual factors. During the growing season, clover experiences the weather conditions of June for the first cutting and the end of July and August for the second cutting. This made it possible to obtain a multifactorial statistical dependence of meadow clover seed yields on a complex of meteorological values.